The Influence Of Human Resources Competency And Performance Management Systems Towards Performance Employee Hotel Narita Surabaya - Aldy Januar Rakhmadi (NAROTAMA UNIVERSITY, Indonesia, 2019)
The aim of this research to analyze the competenceof human resources and performance management System thatsupported simultane and partial performance of employees.Population on this object 40 employess with data retrieval usingthe questionnaire. This research data analysis using the methodof regression with data processing softwere Statistical Packagefor Social Science (SPSS) V 23.0. Research results generatesignificant influence through partially and simultaneous testwith standard T table of 2.253. HA = HR competencies had asignificant influence on performance of employees obtained thenumbers T-count of 5.820, Ha = management system had asignificant influence on performance of employees obtained thenumbers T-count of 2.563, results of 65.7% R2 means theability independent variables in explaining dependent variablesare very high. so, all of the free variable is able to prove theexistence of the influence in the performance of the employeesat Narita Hotel Surabaya.